Long saphenous vein harvesting techniques and their effect on graft patency. Issue 9 (12th July 2019) - Harky, Amer; MacCarthy‐Ofosu, Beverly; Grafton‐Clarke, Ciaran; Pousios, Dimitrios; Muir, Andrew D.
Abstract: Coronary artery bypass grafting is a key cardiac surgery procedure and is the main treatment for patients with multivessel coronary artery disease. The most frequently used conduit for this procedure is the long saphenous vein (LSV). The technique of harvesting the LSV has evolved over the last 30 years from total open harvesting to endoscopic with minimal access technique. The most important determining factor for success in coronary artery surgery is the graft patency rate. The literature evidence behind each technique has been reported at different levels and there is an ongoing debate about which technique can provide optimum vein patency over the long term. This literature review aims to summarize the current evidence, the implications involved with the use of each technique for harvesting LSV and the patency rate at variable follow‐up intervals.